PEMBINGKAIAN BERITA MEDIA ONLINE (ANALISIS FRAMING PEMBERITAAN MEDIA ISLAM RADIKAL PERSPEKTIF BNPT) - Nurhidayat Muh. Said (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2021)
The preparation of news published by Islamic sites related to the problems of the Islamic world, democracy and various aspects of life is by using framing or framing. Examples of middle east conflict cases, from some online media can be read through headlines and news leads made. Then the difference in framing the news can be read through the selection of words, paragraphs, propositions, and main sentences.